Efektivitas Aplikasi Berbasis Microsoft Excel dalam Meningkatkan Pengelolaan Program Kerja dan Wawancara Kepala Madrasah - Hamsah, Hamsah (Green Publisher Indonesia, 2024)
The Excel-based application discussed in this article is designed to make it easier to manage madrasah head interviews and prepare madrasah work programs. This application consists of several sheets that store important data such as personal data of the madrasah and the head of the madrasah, details of the work program, and technical instructions for conducting interviews. This application provides convenience in data storage, processing, and visualization, so that it is able to increase efficiency and accuracy in the preparation of madrasah work programs. The method used in this study is a mixed research method. Mixed method research can be used to research how Excel applications affect the efficiency of madrasah heads. The results of the conclusion stated that this Microsoft Excel-based application has proven to provide a simple but effective solution for the management of madrasah head interviews and the preparation of madrasah work programs.